Resistencia social en Colombia : entre guerra y neoliberalismo (2011)
ABSTRACT: In order to understand the process underlying the Colombian social resistance (2000-2010), the writer proposes an analysis of the “armed neoliberalism” impact. The social and political cost of implementing this economic model represents so high a degree of depolitisation that the possibility of direct political influence practically disappears. Additionaly, the war policy pursued by the Colombian government against guerrillas has multiple consequences, including the diversion of funds from the welfare budget to the war, and population transfers –which ultimately favour latifundia (landowners’ agrarian structure)–, ie it entails a social marginalisation process with high poverty rates. Hence, civil resistance hinges upon one single demand: “safety”, which is not homogeneous in form. In the writer’s words, these are “fragmented expressions” awaiting political opportunity for real participation.